Building a state of the art laboratory for teaching and research in renewable electric energy systems and microgrids - Rajakaruna, Sumedha; Islam, S. (2011)
Green Electric Energy Park at Curtin University will be a state of the art renewable energy systems integration laboratory. It is designed such that the characteristics of each renewable energy source such as solar photovoltaic arrays, wind turbines, micro-hydro turbines and fuel cell stacks can be measured digitally, displayed and analysed on workstation computers and central displays when they are supplying power to isolated dc or ac loads, charging batteries, connected to the main grid or operating as an isolated micro-grid. Weather conditions and all system variables such as voltage and current at all the nodes of the electrical network are measured and made available through the local area network and over the internet for students to analyze at the laboratory classes and also to display graphically in lecture theatres. All the feeds from renewable energy sources and network operating conditions are also made available to research stations where new ways of combining, controlling and converting renewable energy sources will be experimented. This paper briefly describes the need of the facility, the concept of design, laboratory classes made possible and the challenges faced in implementing the project.